The Hegemonic Identity and State Interests in the United States’ TikTok Ban Policy (2020) - Oddie Bagus Saputra; Hla Moe Tara Hlaing (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This article examines the United States’ TikTok ban policy in 2020 by analyzing the relationship between hegemonic identity, state interests, and foreign policy actions. Drawing upon a constructivist perspective, the study argues that the policy should not be understood solely as a technocratic response to cybersecurity concerns, but rather as part of a broader effort to preserve the United States’ dominant position within the global technological order. The United States’ identity as the hegemonic power shaped the construction of strategic interests related to cybersecurity, digital sovereignty, and platform competition, which were subsequently translated into the restrictive policy measures targeting TikTok as the Chinese-owned platform. Using a qualitative case study approach, this article analyzes policy documents, official government statements, and relevant academic literature concerning digital politics and US–China technological rivalry. The findings demonstrate that the TikTok ban reflected broader geopolitical anxieties regarding China’s technological rise and the shifting balance of power within the global digital economy. This article contributes to International Relations scholarship by highlighting the role of identity in shaping foreign policy behavior in the context of digital capitalism and technological competition.